2007
DOI: 10.1080/20786204.2007.10873650
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of injuries suffered by patients treated for alleged assault at Witbank General Hospital, Mpumalanga

Abstract: BackgroundViolence has been with us since time immemorial. In South Africa, violence plays a detrimental role in our daily lives, affecting almost everybody, directly or indirectly. The country experiences high levels of violence, with incidents of violence being reported in the newspapers and on radio and television on a daily basis. In the author's personal experience as a casualty officer at Witbank General Hospital, a considerable number of patients with assault-related injuries were seen every day. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
2
5
2
Order By: Relevance
“…This is similar to findings in South Africa, England and Denmark (3,5,7,9,10). Upper limb was the second commonest site in the index study, which is similar to observations in South Africa and England, but different from reports from India and Scotland (1)(2)(3)(4)(5)(6)(7)10). That the UL is second most involved site may possibly be due to the defensive and instinctive reaction of humans toward an external attack by simply extending the upper limbs (1,2).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This is similar to findings in South Africa, England and Denmark (3,5,7,9,10). Upper limb was the second commonest site in the index study, which is similar to observations in South Africa and England, but different from reports from India and Scotland (1)(2)(3)(4)(5)(6)(7)10). That the UL is second most involved site may possibly be due to the defensive and instinctive reaction of humans toward an external attack by simply extending the upper limbs (1,2).…”
Section: Discussionsupporting
confidence: 77%
“…Other studies in South Africa, Scotland, England and Denmark reported fist as the most commonly used instrument (3,4,7,9,10). Various studies in India reported sharp objects, sticks and other blunt objects as most commonly used (1,2,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that most HCPs fall within the highest tax bracket in South Africa may influence them to think that alcohol intoxication (being self-inflicted) and the resultant injuries unfairly place a substantial financial burden on taxpayers and consume resources that could be devoted to other illnesses. 13,14 Therefore, alcohol abuse needs to be addressed at different levels to prevent injury and the accompanying costs, so that much-needed resources can be redirected to other health priorities. HCPs' perceptions that these patients place a financial burden on taxpayers and that it is useless to treat them could result in HCPs providing suboptimal treatment, a situation that might result in medico-legal issues.…”
Section: Discussionmentioning
confidence: 99%